Awareness and sources of the digital transactions schemes: a cross sectional study in a rural block of Jabalpur, Madhya Pradesh, India - Tomar, Shashi Prabha; Dangwal, Nipun; Kasar, P. K. (International Journal of Research in Medical Sciences, 2020)
Background: India is a developing country and is on the road of rapid progress, in every aspect. So, to further boost the development process, India joined many other developing countries and showed an intent to promote a cashless economy. However, this penetration is not much in the rural areas which constitute the building blocks of the country. Awareness regarding digital transaction schemes of government of India is imperative to success of such schemes. Hence, the current study for assessing the awareness of the digital transaction schemes and finding out the sources in their implementation will help cater these issues. Methods: A descriptive cross sectional study was conducted among 60 respondents belonging to different age groups, socio economic strata and with different education status, to explore the awareness and acceptance percentage of respondents in rural block Paragraph in relation to digital transaction schemes and methods and the their sources of information. Study was done in three-month duration from1st July 2018 to 30th September 2018. Results: It was found that the awareness for mobile banking among all the age groups was a massive 93.36% while that of the Digital Dakiya scheme is a meagre 8.30%.It was inferred from the study that social interaction was the major information source (51%) and there was a significant association between the use of mobile banking and younger age of the individual. Conclusions: Awareness among the older population and rural females is lesser as compared to counterparts and was massive for mobile banking. Disparity about awareness the of schemes points that overall usage needs to be promoted.